Is being 'soft on crime' the solution to rising crime rates? Evidence from Germany - Horst Entorf; Hannes Spengler (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Based on a theoretical framework on informal, custodial and non-custodial sentencing, the paper provides econometric tests on the effectiveness of police, public prosecution and courts. Using a unique dataset covering German states for the period 1977- 2001, a comprehensive system of criminal prosecution indicators is derived and subsequently related to the incidence of six major offence categories using panel-econometrics. Empirical evidence suggests that the criminal policy of diversion failed as increasing shares of dismissals by prosecutors and judges enhance crime rates in Germany. Crime is significantly deterred by higher clearance and conviction rates, while the effects of indicators representing type (fine, probation, imprisonment) and severity (length of prison sentence, amount of fine) of punishment are often small and insignificant.
Keywords: 330; Kriminalpolitik; Reform; Kriminalität; Schätzung; Deutschland